Peningkatan Jaringan Kemitraan Kelompok Wanita Pengolah Produk Hasil Perikanan di Pantai Kuwaru Bantul - Agustina Setyaningrum; Ernastin Maria (Institut Pertanian Bogor, 2022)
A group of female fishery in Kuwaru Beach, Bantul processes fishery products into processed products that have a higher economic value. The problems faced by the group are limited marketing and PIRT permits. The purpose of this Community Partnership Program (PKM) is to build a network of partnerships so that the female fishery group become independent and competitive. Initial identification was carried out through in-depth interviews with group leaders and focus group discussions with all group members. The method of the program includes training to improve product quality, PIRT management, digital marketing training, building networks, and the use of a fish meat grinder. The results of this activity are partners have ability to build partnership networks with various institutions, namely local governments, the private sector, and universities. In addition, the group as our partners have been able to use digital marketing in marketing their products and the tools provided to partners make them able to produce processed fish creations, so as to increase the competitiveness of the products produced.